Performance of Jatropha (Jatropha curcas L.) based agroforestry system under rainfed conditions - Kaushik, N.; Kumar, Krishan; Kumar, Sushil; Deswal, R.P.S.; Deswal, A.K. (Indian Journal of Agroforestry, 2020)
A field experiment was conducted during the Kharif season of 2005-06 at Regional Research Station, Bawal, Haryana to study the effect on productivity of different crops in a Jatropha based agroforestry system under rainfed conditions. Maximum green fodder yield was recorded in daincha (24.00 and 24.10 t/ha during the year 2005 and 2006, respectively) followed by pearl millet which was significantly higher than other crops. The trend of variation in dry matter yield offodder crops under the influence of Jatropha canopy was similar to green fodder yield. The grain yield for all arable crops was at par in association with and without Jatropha. Maximum grain yield (1.35 Uha 2005, 1.30 Uha 2006) was harvested from pearl millet in association with Jatropha which was statistically at par when the pearl millet was raised as sole. Minimum height (170.00 cm), crown spread (179.00cm) and number of branches (34.00) were recorded when the Jatropha was intercropped with pearl millet.